STUDI NETNOGRAFI TERHADAP KOMENTAR HOMOFOBIA DI INSTAGRAM @GITASAV DALAM KONTEN INTERNATIONAL WOMEN'S DAY 2023 - Putra Pratama Nabasa (2023)
This research aims to determine a netnographic study of homophobic comments on Instagram @gitasav on the content of International Women's Day 2023 using computer-mediated communications (CMC) theory, feminist standpoint theory, and reception theory. The method used is descriptive qualitative research with netnographic methods using primary and secondary data sources. The sampling technique was carried out by observation, document analysis, and literature study. Researchers used six stages of data analysis according to Kozinets, namely coding, recording, abstraction and comparison, checking and refinement, generalization, and theory. The final results from this research showed that 44% of the comments were positive, followed by 35% of neutral comments. Then negative comments amounted to 20%. Positive negative comments were 1% and negative positive comments were 0.19%. After being classified with the Reception Theory by Stuart Hall, 236 comments were selected to be in the Dominant Hegemony position, 107 comments were in the Opposition position and 8 comments were in the Negotiation position. There is a tendency for netizens to accept Gitasav's content in their uploads celebrating International Women's Day 2023, although, at the same time, negative comments such as insults, sarcasm, foul language, disappointment, and homophobia towards Gitasav and the LGBTQ+ community also still fill the comments column, drawing the point of view that Gitasav is no longer seen as the Muslim woman she has always been attached to.